Building a form of assessing ICT capacities of professional and trade schools teachers - Do, Mạnh Cường (Journal of Technical Education Science, 2009)
Evaluating the technical teacher’s competence in their application of information and communication technology (ICT) requires a suitable and reliable model. But how to build it? By analyzing and comparing some existing models, we can build an evaluation model for our purpose. This model will serve as a base in designing the necessary survey tools.